SAFETY OF ORAL DOXYCYCLINE TREATMENT IN NILE TILAPIA, Oreochromis niloticus - OLIVEIRA, S. L.; COSTA, C. C.; CONDE, G.; ARACATI, M. F.; RODRIGUES, L. F.; SILVA, I. C.; COLTURATO, L.; MONTASSIER, H. J.; BELO, M. A. A. (Ars Veterinaria, 2022)
This study aimed to evaluate the clinical safety of doxycycline treatment (Sandoz Pharmacetical Industry from Brazil Ltd.), administered orally incorporated into the feed of Nile tilapia, Oreochromis niloticus. For this purpose, 75 Nile tilapia (± 300g) from the same spawning were randomly distributed in 15 tanks (n=5), containing 100 L of water each, supplied with running water free from chlorine, to establish the following treatments: T0 (Control - not treated with doxycycline); T1, T2, T3 and T4 (treated with 10, 20, 40 and 80mg of doxycycline/kg of body weight, respectively), in which 5 animals per treatment were sampled in 3 periods: 2, 4 and 8 days post-treatment (DPT). Blood samples were collected for hemogram determination and serum biochemical evaluation, as well as spleen, liver and kidneys (cranial and caudal) for somatic and histopathological evaluation. The results showed no significant difference among treatments in the serum values of creatinine, total protein, cholesterol, triglycerides, globulin, glycemia and alkaline phosphatase enzyme activity. However, serum levels of AST (aspartate aminotransferase) were significantly higher (P<0.05) in animals treated with 80 mg of doxycycline in the longest period of treatment (8 days). In the hematological evaluation of tilapia treated with doxycycline, no significant changes (P>0.05) were observed in erythrocyte counts, hematocrit, MCV, HCM and CHCM values. Doxycycline-treated tilapia did not present significant difference in the somatic analysis of spleen, liver and kidney when compared to control group. Therefore, the results demonstrated the clinical safety of oral treatment with doxycycline at doses of 10, 20, 40 and 80 mg/kg of b.w., although transient changes in liver functionality were observed after eight days of treatment with the dose of 80mg/kg.